Macroeconomic and Welfare Effects of Public Infrastructure Investment in Five Latin American Countries - Carlos Gustavo Machicado (Institute for Advanced Development Studies (INESAD), 2007)
It has been widely documented that investment in infrastructure is important for economic growth, but little work has been done in relation to the impact of infrastructure investment on other macroeconomic variables. This paper develops a Dynamic Stochastic General Equilibrium (DSGE) model of a small open economy to study the effects of public investment in infrastructure on output, consumption, private investment, trade balance and welfare. The model is parameterized and solved for five representative countries from The Initiative for the Integration of Regional Infrastructure in South America (IIRSA), which include: Bolivia, Chile, Brazil, Venezuela and Argentina. I also analyze the growth effects on GDP by increasing or decreasing the effectiveness index of infrastructure in each of these countries. Naturally output will grow at a larger rate, if infrastructure is handled with greater efficiency.
Keywords: H54; O40; D60; 330; Infrastructure; Economic Growth; Welfare